PENGGUNAAN LEARNING MANAGEMENT SYSTEM PADA PEMBELAJARAN ARITMATIKA SOSIAL DALAM MENINGKATKAN KEMANDIRAN BELAJAR SISWA MADRASAH TSANAWIYAH DI KOTA MEDAN - Muhammad Badzlan Darari; Suci Frisnoiry (Universitas Negeri Medan, 2021)
Abstract: The benefit of this research is to find out the increase in learning independence of Madrasah Tsanawiyah students in Medan City through the use of the Learning Management System on social arithmetic material. Independent learning is a learning that is needed by students in the brave process. Student learning independence can be interpreted as a condition where students are fully responsible for the learning process they experience without depending on others. Learning independence is a condition where students are able to take the initiative in diagnosing their own learning needs, formulate learning for themselves, identify various supporting sources and materials for learning, select and implement appropriate learning strategies for themselves, determine learning resources and materials. The design of this study was a quasi-experimental with Non-equivalent control group design. Samples were taken from two private Madrasah Tsanawiyah in Medan City which were divided into experimental groups and control groups. The research instrument used in this study was a learning independence questionnaire that was learned from Muray Fisher and consisted of 40 questions. After being declared valid and reliable, a questionnaire was given to the research sample students at the beginning of the study and at the end of the study (pretest and posttest). The average N-gain score was obtained for each experimental group and control group. The average difference test was performed using the t-test after the N-gain data was declared to be normally distributed and have homogeneous variance. The results of the Independent Sample T Test through SPSS show that there are differences in the learning independence of Madrasah Tsanawiyah students in social arithmetic material between students who are taught using online LMS and students who are taught using LKS in an attractive way. Keywords: Learning Management System, Independent Learning, Social Arithmetic Abstrak: Manfaat dari penelitian ini adalah mengetahui peningkatan kemandirian belajar siswa Madrasah Tsanawiyah di Kota Medan melalui penggunaan Learning Management System pada materi aritmatika sosial. Kemandirian belajar merupakan sebuah kecakapan yang sangat dibutuhkan oleh siswa dalam proses pembelajaran daring. Kemandirian belajar siswa dapat diartikan sebuah kondisi dimana siswa bertanggung jawab secara penuh terhadap proses pembelajaran yang dialaminya tanpa bergantung pada orang lain. Kemandirian belajar merupakan kondisi dimana siswa mampu mengambil inisiatif dalam mendiagnosis kebutuhan belajar mereka, merumuskan tujuan pembelajaran bagi mereka sendiri, mengidentifikasi berbagai sumber pendukung dan materi untuk belajar, memilih dan menerapkan strategi belajar yang sesuai untuk dirinya, menentukan sumber dan bahan belajar. Desain penelitian ini adalah eksperimen semu dengan Non-equivalent control group design. Sampel diambil dari dua Madrasah Tsanawiyah Swasta di Kota Medan di bagi menjadi kelompok ekseprimen dan kelompok kontrol. Instrumen penelitian yang digunakan pada penelitian ini adalah angket kemandirian belajar yang dimodifikasi dari Muray Fisher dan terdiri dari 40 butir pertanyaan. Setelah dinyatakan valid dan reliabel, angket diberikan kepada siswa sampel penelitian di awal peneltian dan diakhir penelitian (pretest dan posttest). Diperoleh rata-rata skor N-gain untuk masing-masing kelompok eksperimen dan kelompok kontrol. Dilakukan uji beda rata-rata menggunakan uji-t setelah data N-gain dinyatakan berdistribusi normal dan memiliki varians yang homogen. Hasil uji Independent Sample T Test melaui SPSS menjunjukkan bahwa terdapat perbedaan kemandirian belajar siswa Madrasah Tsanawiyah pada materi aritmatika sosial antara siswa yang diajarkan menggunakan LMS secara daring dan siswa yang diajarkan menggunakan LKS secara luring. Kata kunci : Learning Management System, Kemandirian Belajar, Aritmatika Sosial